Educational cooperation of Spain with foreign countries and their experience for Russia - Viktoria Kuznetsova (Ибероамериканские тетради, 2018)
Spain’s higher education system is researched in the context of the globalization of contemporary international society life. The educational policy implemented in Spain is part of a strategy that is applied throughout the world to improve the knowledge and skills of the entire population, especially the new generation. The cooperation of Spain in the educational sphere with such countries, as the United States, Germany, Mexico, China and international organizations, represents practical interest for Russia, which is developing the public project «5-100» to increase the competitiveness of the leading Russian universities.